The potential ecological effects of casein phosphopeptide‐amorphous calcium phosphate in dental caries prevention. (22nd November 2018) - Philip, N; Walsh, L
Abstract: Contemporary caries prevention protocols recommend not only effective remineralizing agents but also ecological measures to reverse the dental plaque dysbiosis responsible for the disease pathogenesis. There is a high‐level of evidence supporting the remineralizing efficacy of casein phosphopeptide‐amorphous calcium phosphate (CPP‐ACP) from studies around the world. Evidence is now emerging that CPP‐ACP may also have a beneficial influence on the dental plaque microbial ecology and homeostasis. The ecological cariostatic effects of CPP‐ACP are believed to be mediated predominantly through its anti‐adhesion, buffering and biofilm disrupting actions. This review principally discusses the ecological mechanisms of CPP‐ACP and presents the current evidence for its effects on the oral microbiome ecology.